The importance of updating quality tools in methodologies applied in industry 4.0 (Research, Society and Development, 2021)
The revolutions and, consequently, industrial developments allow us a vast academic and organizational growth promoting the promotion of discussions on several subjects, in principle in theory and later taking them to practice. Understanding these new technologies becomes the great challenge for managers today where to interface the management tools already known and applied, adapting those to come. The methodology used in this article was that of quantitative research, which is the one in which the data and evidence collected can be quantified and measured. The aim of the work is to encourage discussion about quality tools in industry 4.0. It is concluded that there is still a lot to analyze, discuss and improve on the application of an update of the quality tools with regard to the new world of methodologies 4.0, always in the search for greater efficiency and effectiveness of the productive and administrative processes in the various sectors, but as a topic presented that should be addressed in the academic environment and in companies.